2004
DOI: 10.2460/ajvr.2004.65.1573
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of haplotypes associated with copper toxicosis in Bedlington Terriers in Australia

Abstract: Our findings indicate that the deletion of exon 2 was not the sole cause of copper toxicosis, although only exon 2 deletion of Murr1 has been responsible for copper toxicosis in Bedlington Terriers. Although we failed to find a novel mutation in our cohort, we identified an affected dog family with an intact exon 2. Furthermore, we found that an SNP in the 5' splicing site of exon 2 may or may not be associated with a novel mutation of the Murr1 gene or other genes. Loss of linkage between the C04107 marker an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 19 publications
0
13
0
Order By: Relevance
“…Recently, however, some ct -affected Bedlington terriers have been identified without the homozygous commd1 deletion in both the uk , usa and Australia (Coronado and others 2003, Hyun and others 2004), reinforcing earlier voiced concerns. Since no other commd1 mutation could be found in them, we (Haywood and van de Sluis) have hypothesised that a second as yet unknown disease gene is involved in Bedlington ct and have received funding from the Kennel Club to try to identify this gene.…”
mentioning
confidence: 87%
“…Recently, however, some ct -affected Bedlington terriers have been identified without the homozygous commd1 deletion in both the uk , usa and Australia (Coronado and others 2003, Hyun and others 2004), reinforcing earlier voiced concerns. Since no other commd1 mutation could be found in them, we (Haywood and van de Sluis) have hypothesised that a second as yet unknown disease gene is involved in Bedlington ct and have received funding from the Kennel Club to try to identify this gene.…”
mentioning
confidence: 87%
“…Deficiency of Murr1 is the main cause for copper toxicosis in dogs, 1,26,69,70 and co-precipitation experiments suggest a direct interaction with the WDP. 30 -32 In our hands, there was no co-localization between Murr1/ COMMD1 on membrane vesicular structures and ATP7B (Figure 4, A-C).…”
Section: Discussionmentioning
confidence: 99%
“…Positional cloning efforts determined that an~10 kb deletion involving exon 2 of the COMMD1 gene is associated with the disease phenotype in European pedigrees [5] , and subsequent studies in Australia have observed that all dogs homozygous for this deletion develop the disorder [40] . Consistent with a disease-causing role for this COMMD1 mutation, the protein is absent in affected animals that are homozygous for the exon 2 deletion [8] .…”
Section: Commd1 As a Regulator Of Copper Metabolismmentioning
confidence: 99%
“…Moreover, reduction of COMMD1 expression by RNA interference results in increased accumulation of copper in human embryonic kidney cells [7] and in dog hepatic cells [41] , supporting the notion that COMMD1 plays a role in the control of intracellular copper levels. More recently, it has been demonstrated that not all affected Bedlington terriers carry a deletion in exon 2 of the COMMD1 gene; some affected animals are heterozygous for the COMMD1-deleted state or even carry two alleles without this deletion [40,42]. To date, no disease-causing mutations have been found in the COMMD1 coding sequence or splice sites of nondeleted alleles that segregate with the disorder, raising questions about the nature of the mutation that results in copper toxicosis in these animals.…”
Section: Commd1 As a Regulator Of Copper Metabolismmentioning
confidence: 99%